Cub in the cupboard - Baglio, Ben M. (New York : Scholastic, Inc., 1994)
While her parents treat an injured fox in their veterinary hospital, Mandy cares for the fox's cub and tries to stop a farmer from setting steel traps and organizing a fox hunt.
"An Apple paperback."
Keywords: Animals -- Fiction; Foxes -- Fiction; Fiction; Fiction